(untitled) (Advances in Military Technology, 2022)
Techniques for forecasting extreme temperature are mostly empirically based, using collections of statistics over a long period of time for a range of weather situations. In the article we have used the McKenzie’s method for forecasting the minimum temperature and Callen and Prescott’s method for forecasting the maximum temperature. Both of methods belong among the successfully and routinely used techniques. Main aim is to adjust these methods for routine application on aerodromes currently used by Czech Air Force.